2019
DOI: 10.1016/j.jare.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from the stems of Millettia pachyloba Drake mediate cytotoxic activity through apoptosis and autophagy in cancer cells

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…A number of studies have revealed that flavonoids could induce apoptosis in various cancer cells [24][25][26]. In the present study, we also detected obvious apoptosis in HeLa cells upon the administration of flavonoids in A. conyzoides.…”
Section: Discussionsupporting
confidence: 76%
“…A number of studies have revealed that flavonoids could induce apoptosis in various cancer cells [24][25][26]. In the present study, we also detected obvious apoptosis in HeLa cells upon the administration of flavonoids in A. conyzoides.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, isoflavones extracted from M. taiwaniana have shown cancer chemopreventive activities [20]. Durmillone isolated from M. pachyloba Drake induced apoptosis and autophagy in Hela and MCF-7 cells [21]. In this study, we demonstrated that two isoflavones, ferrugone and DMI, isolated from M. ferruginea, induced apoptotic cell death in human ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 52%
“… 25 To further determine how HTPM reduces the viability of breast cancer cells, Annexin V-FITC/PI double staining was performed to assess the extent and mode of cell death. 35 In this study, MDA-MB-231 cells were treated with various concentrations of HPTM ranging from 0 to 50 nM, and then the percentage of apoptotic cells was quantitatively analyzed by flow cytometry. As depicted in Figure 5A – B , HTPM lead to apoptosis, including early and late apoptosis after exposure for 24 h. The apoptotic levels of MDA-MB-231 cells were gradually enhanced with increased treatment concentrations.…”
Section: Resultsmentioning
confidence: 99%